Acute Effects of Different Exercise Protocols on the Circulating Vascular microRNAs -16, -21, and -126 in Trained Subjects - Wahl, Patrick; Wehmeier, Udo F.; Jansen, Felix J.; Kilian, Yvonne; Bloch, Wilhelm; Werner, Nikos; Mester, Joachim; Hilberg, Thomas (Frontiers in Physiology, 2016)
Aim mircoRNAs (miRNAs), small non-coding RNAs regulating gene expression, are stably secreted into the blood and circulating miRNAs (c-miRNAs) may play an important role in cell–cell communication. Furthermore, c-miRNAs might serve as novel biomarkers of the current vascular cell status. Here, we examined how the levels of three vascular c-miRNAs (c-miR-16, c-miR-21, c-miR-126) are acutely affected by different exercise intensities and volumes. Methods 12 subjects performed 3 different endurance exercise protocols: 1. High-Volume Training (HVT; 130 min at 55% peak power output (PPO); 2. High-Intensity Training (HIT; 4x4 min at 95% PPO); 3. Sprint-Interval Training (SIT; 4x30 sec all-out). c-miRNAs were quantified using quantitative real-time PCR with TaqMan probes at time points pre, 0´, 30´, 60´ and 180´ after each intervention. The expression of miR-126 and miR-21 was analyzed in vitro, in human coronary artery endothelial cells, human THP-1 monocytes, human platelets, human endothelial microparticles (EMPs) and human vascular smooth muscle cells (VSMCs). To investigate the transfer of miRNAs via EMPs, VSMCs were incubated with EMPs. Results HVT and SIT revealed large increases on c-miR-21 (1.9-fold by HVT (cohen’s d = 0.85); 1.5-fold by SIT (cohen’s d = 0.85)) and c-miR-126 (2.2-fold by SIT (cohen’s d = 1.06); 1.9-fold by HVT (cohen’s d = 0.85)) post exercise compared to pre values, while HIT revealed only small to moderate changes on c-miRs-21 (cohen’s d = -0.28) and c-miR-126 (cohen’s d = 0.53). c-miR-16 was only slightly affected by SIT (1.4-fold; cohen’s d = 0.57), HVT (1.3-fold; cohen’s d = 0.61) or HIT (1.1-fold; cohen’s d = 0.2). Further in vitro experiments revealed that miR-126 and miR-21 are mainly of endothelial origin. Importantly, under conditions of endothelial apoptosis, miR-126 and miR-21 are packed from endothelial cells into endothelial microparticles, which were shown to transfer miR-126 into target vascular smooth muscle cells. Conclusion Taken together, we found that HVT and SIT are associated with the release of endothelial miRNAs into the circulation, which can function as intercellular communication devices regulating vascular biology.